2012
DOI: 10.1007/s10616-012-9467-9
|View full text |Cite
|
Sign up to set email alerts
|

Improving the attachment and proliferation of umbilical cord mesenchymal stem cells on modified polystyrene by nitrogen-containing plasma

Abstract: Wharton's jelly mesenchymal stem cells (WJMSCs) are important alternative source of pluripotent cells for several therapeutic purposes. Understanding of adhesion properties of such cells is necessary to regulate the attachment, growth and proliferation on targeted culture surfaces. BCP-K1, a line of WJMSCs, and polystyrene (PS) culture dishes were used as membrane samples. A 13.56 MHz inductively coupled discharge plasma reactor with a mixture of N-containing gas and noble gas was used. This was expected to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…Initial cell attachment plays an important role in further cell viability on biomaterials; thus the pattern of architecture and surface properties of the materials are crucial [ 29 ]. Although most of the observed WJMSC of this study appeared as separated, single, attached cells, some colonies were still found on the surfaces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial cell attachment plays an important role in further cell viability on biomaterials; thus the pattern of architecture and surface properties of the materials are crucial [ 29 ]. Although most of the observed WJMSC of this study appeared as separated, single, attached cells, some colonies were still found on the surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…BCP-K1 (hWJMSC line) was obtained from the Human and Animal Cell Technology Research Laboratory, Department of Biology, Faculty of Science, Chiang Mai University, Thailand. The cells were cultured in a complete medium, supplemented with 10% (w/v) fetal bovine serum and essential growth factors and maintained as described in Tunma et al [ 29 ]. Briefly, the medium was replaced every 2 days; trypsinization was performed when cell density reached around 70–80% of the culture surface.…”
Section: Methodsmentioning
confidence: 99%
“…Plasma treatment was shown to be a very effective method to increase adhesion of different cell types on various biomaterials 40,41 . Oxygen plasma treatment is commonly used to introduce hydrophilic surfaces onto fabricated polymers.…”
Section: Surface Chemical Modification By Plasma Treatmentmentioning
confidence: 99%
“…In fact, corrosion of the polymeric surface could occur, and this might affect the 3D macrostructure of the PCL scaffold. This approach has been successfully used for scaffold engineering to provide functionalization of the surface with primary amines, even if keeping bulk properties of the virgin polymeric material, and also to enhance cell adhesion properties of hydrophobic polymers [22,[28][29][30]. Furthermore, primary amines also allow monolayer covalent deposition of GO through the reaction with epoxy groups intrinsically contained in GO sheets [31].…”
Section: Surface Functionalization Of Pcl Patch With Go Via Nonthermamentioning
confidence: 99%